SENYAWA ANTIBAKTERI YANG DIPRODUKSI OLEH LACTOBACILLUS PLANTARUM DAN APLIKASINYA UNTUK PENGAWETAN BAHAN IKAN - Sulistiani, Sulistiani (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTLactic acid bacteria (LAB) generally accepted as safe microorganism and play an important role in the fermen-tation and preservation of food/feed. LAB is known to extend the shelf life of food/feed, because of its ability to produce antibacterial compounds such as lactic acid, hydrogen peroxide and bacteriocins. The objective of this study was antibacterial compounds produced by Lactobacillus plantarum and their application for fish preserva-tive. The research results showed L. plantarum [Su-ls520, Su-ls530, Su-ls537] produces lactic acid from 71.16 to 77.91mg/mL, hydrogen peroxide from 0.17 to 0.25 mg/mL and producing bacteriocins indicated by the pres-ence of the gene encoding plantaricin, an antibacterial compounds that act as food preservative. Lactic acid 1.5% and 3% salt was not able to suppress the growth of bacteria, while fermentation solution (supernatant) of L. plantarum [Su-ls520, Su-ls530], chitosan 1.5% and a mixture of lactic acid 1.5% and salt 3% slightly sup-press the growth of spoilage bacteria on the fish material stored 48 hours at room temperature. Treatment with fermentation solution (supernatant) of L. plantarum Su-ls537 able to suppress strongly growth of spoilage bac-teria in fish material for 24 and 48 hours storage. At 72 hours of storage the fish material rotted, the addition of preservatives no longer able to suppress the growth of spoilage bacteria.Keywords: lactic acid bacteria (LAB), Lactobacillus plantarum, fish, antibacterial compounds, preservation